Evaluasi Inovasi Pandawa dengan Perspektif Logic Model pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Pasaman Barat - Aromatica, Desna; Ariany, Ria; Alifya, Falina (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2024)
Public services of activities aimed at meeting the service needs of every citizen. One effort to support the creation of quality public services is through digital-based innovation by making maximum use of developments in information technology. The West Pasaman Regency Population and Civil Registration Service initiated the PANDAWA innovation, which is a form of digital-based innovation as a form of application of the e-Government concept. The theory used by researchers is the Logic Model by Wholey. A logic model is a systematic model to describe the changes that occur, and describes the logical causal relationship (cause-effect). There are four components of this theory, namely evaluation of input, activities, output, and results. The research method used is descriptive qualitative. To collect data, researchers used three methods, namely interviews, documentation and observation. Research informants were selected using purposive sampling. The results research are that the evaluation of the PANDAWA program from the input components to the output components is quite good. However, in the input component, service facilities need to be added, clarifying the partnership system established with the parent village; In the activity component, it is necessary to increase socialization activities related to PANDAWA both directly and through mass media. So that the output of this program has increased and the entire West Pasaman community can experience the ease of PANDAWA services evenly and the realization of excellent service at the West Pasaman Regency Population and Civil Registration Service.